A social - ecological analysis of comunity perceptions of dengue fever and Aedes Aegypti in Machala, Ecuador. - Beltrán, Ayala Efraín (United Kingdom, 2014)
The growing burden of dengue fever and the lack of a vaccine or specific medical treatment have increased the urgency of the public health sector to identify alternative management strategies. A prevailing trend in Latin America has been a shift towards decentralized vector control programs with integrated management strategies, requiring significant intersectoral coordination, community engagement, and knowledge of the local social-ecological system (SES). Community perceptions and responses are a critical component of this system, since perceptions shape actions, and thus govern behavioral responses and acceptance of shifts in policy and management.
Keywords: BMC Infectious Diseases; DENGUE; MACHALA; ECUADOR